Refusing care as a legal pathway to medical assistance in dying - Jocelyn Downie; Matthew J Bowes (Canadian Journal of Bioethics, 2019)
Can a competent individual refuse care in order to make their natural death reasonably foreseeable in order to qualify for medical assistance in dying (MAiD)? Consider a competent patient with left-side paralysis following a right brain stroke who is not expected to die for many years; normally his cause of death would not be predictable. However, he refuses regular turning, so his physician can predict that pressure ulcers will develop, leading to infection for which he will refuse treatment and consequently die. Is he now eligible for MAiD? Consider a competent patient with spinal stenosis (a non-fatal condition) who refuses food (but not liquids in order not to lose capacity from dehydration). Consequently, her physician can predict death from starvation. Is she now eligible for MAiD? Answering these questions requires that we answer three sub-questions: 1) do competent patients have the right to refuse care?; 2) do healthcare providers have a duty to respect such refusals?; and 3) are deaths resulting from refusals of care natural for the purposes of determining whether a patient is eligible for MAiD? If a competent patient has the right to refuse some particular care, and healthcare providers have a duty to respect that refusal, and if the death that would result from the refusal of that care is natural, then that refusal of care is a legal pathway to MAiD. However, if the competent patient does not have the right to refuse some particular care, or if healthcare providers do not have a duty to respect that refusal, or if the death that would result from the refusal of that care is not natural, then that refusal of care is not a legal pathway to MAiD. In this paper, we explore this complex legal terrain with the most profound of ethical implications – access to MAiD.